Managing the Public Sector Wage Bill during COVID-19 - World Bank (World Bank, Washington, DC, 2020)
The Coronavirus 2019 (COVID-19) crisis is unique and requires tough policy choices for managing the public sector wage bill to best achieve the difficult balance between fiscal consolidation, protection of lives and livelihoods, service delivery, and job restoration. In the emergency phase, the priority should be on protecting lives and livelihoods. Short-term measures will likely increase the wage bill. As a result, in the recovery and resilience phase, priority must be given to fiscal consolidation, the reduction of labor market distortions that may hurt private sector job creation, and an increase in the productivity of the public sector so that more outputs are produced per worker. To these ends, the note provides suggestions that countries can adapt based on their circumstances and given that they entered this crisis from different starting points: emergency phase: protect public sector employment and wages, increase staffing for essential functions, and provide adequate compensation for essential workers; and recovery and resilience phase: monitor the public sector wage premium, curtail high pay and remove distortionary allowances, build staffing flexibility and agility, emphasize compensation and management reforms to improve productivity, and leverage technology and data for decision-making.